Water reaction type asphalt cold patch material and preparation method thereof
By using water-reactive composite materials, including modified maleic acid and metal salts in asphalt cold feed, to form a crosslinked structure, the existing problems of insufficient strength and water stability of asphalt cold feed are solved, and high strength, long life and environmentally friendly repair effects are achieved.
Patent Information
- Application Number
- CN202510070165.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing asphalt cold feed has insufficient initial strength and water stability, resulting in unsatisfactory repair results, short service life, and the solvent-based materials used are highly polluted to the environment.
Water-reactive asphalt cold feed is used, and its composition includes aggregates, mineral powder, matrix asphalt, composite initiators and hyperabsorbent resin. It is modified with ethylenediamine or alanine by maleic acid and combined with iron or copper salt to form a crosslinked structure to improve strength and stability.
It significantly improves the initial strength, water stability and service life of asphalt cold feed, while avoiding the use of volatile solvents, achieving environmentally friendly repair results.
Smart Images

Figure CN119874258A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road engineering materials, and in particular to a water-reactive asphalt cold patch material and a preparation method thereof. Background Art
[0002] Asphalt pavement is widely used in highway construction around the world because of its significant advantages such as being able to effectively reduce driving noise, provide a more comfortable driving experience, and be easy to maintain and repair. However, as time goes by, while bearing the traffic load, asphalt pavement also needs to cope with the challenges brought by changes in the natural environment. Asphalt pavement is prone to rutting, looseness, cracks, potholes and other diseases, and these diseases are random, sudden and spreading, which seriously affect the flatness of asphalt pavement, driving comfort and safety, and greatly reduce the service life of asphalt pavement. Therefore, it is very important to carry out timely and effective repair and maintenance of damaged roads.
[0003] For a long time, pavement repair technology has mainly relied on two methods, one is the traditional hot patching method using hot-mix hot-paved asphalt mixture, and the other is the direct application of cold-mix asphalt mixture at room temperature, namely the cold patching method. The traditional hot patching method requires special machinery and experienced operators, and is not suitable for small or decentralized pavement repair projects. In addition, the application of hot-mix asphalt mixtures will be limited in low temperatures, rainy weather or wet pavement. In contrast, cold patching technology overcomes the limitations of traditional hot patching methods. The mixture it uses is prefabricated. When performing pavement repair work on site, there is no need to heat it. It only needs to be simply stirred, spread and compacted, which greatly simplifies the operation process and can be used as needed. It can be used quickly even under poor temperature or environmental conditions.
[0004] The various components used in the cold patching method are collectively referred to as cold patch asphalt mixture, or cold patch material for short. At present, the most widely used solvent-based asphalt cold patch material in my country is usually composed of base asphalt, diluent and additives. After the construction is completed, as the diluent slowly evaporates, the binder in the cold patch material continues to solidify, and is further compacted by the rolling of vehicles after the traffic is opened. However, the slow volatilization rate of the diluent causes the initial strength of the solvent-based asphalt cold patch material to fail to achieve the ideal effect, and it is very easy to peel and fall off. If it is in a rainy and humid environment, it is more likely to be taken away by a moving vehicle, thereby greatly reducing the repair effect and shortening the service life; secondly, the diluent is mostly selected from petroleum products such as gasoline, kerosene, and engine oil, which will also cause pollution to the environment. For example, the Chinese patent application with publication number CN112851174A provides a method for preparing a chemical reaction type cold patch asphalt mixture, which uses the hydration of calcined materials and the generation of fatty acid salts to improve the strength of the cold patch material, but the water resistance and solvent resistance of fatty acid salts are difficult to guarantee. In view of the shortcomings of the current asphalt cold patch material, it is necessary to propose an asphalt cold patch material with good water stability, high strength, long service life and green environmental protection. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a water-reactive asphalt cold patch material and a preparation method thereof.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A water-reactive asphalt cold patch material comprises the following components in parts by weight: 500-600 parts of aggregate, 40-60 parts of mineral powder, 65-120 parts of base asphalt, 0.5-8 parts of composite initiator and 1-10 parts of highly absorbent resin;
[0008] Wherein, the composite initiator is a composition of iron salt or copper salt and maleic acid modified by ethylenediamine or alanine.
[0009] Preferably, the aggregate is limestone ore, and the gradation type of the aggregate is LB-10; the mineral powder is basalt mineral powder.
[0010] Aggregate, as one of the main components of cold patch material, provides structural strength and volume basis for asphalt cold patch material. Limestone aggregate is hard in texture and is an excellent supporting skeleton in water-reactive asphalt cold patch material. Its good wear resistance makes the cold patch material not easy to deform when bearing vehicle load, and the LB-10 grading makes the limestone aggregate form a tight interlocking structure, which helps to maintain the flatness and stability of the repaired road surface. Basalt mineral powder is an alkaline rock mineral powder, which has good adhesion with asphalt, thereby improving the water stability of asphalt cold patch material. Its chemical properties are stable and it is not easy to react adversely with other components, which is conducive to the long-term storage of cold patch material.
[0011] Preferably, the base asphalt is any one of No. 70 base asphalt, No. 90 base asphalt, and No. 110 base asphalt.
[0012] As a binder, the matrix asphalt combines the aggregate and other components in the cold patch material to form a solid whole. The matrix asphalt has an appropriate viscosity, making the cold patch material easy to spread and compact during subsequent construction.
[0013] Preferably, the iron salt is ferric chloride; the copper salt is selected from copper sulfate; the mass of ethylenediamine or alanine is 10-50% of the mass of maleic acid; the mass of ferric chloride or copper sulfate is 20-80% of the mass of maleic acid.
[0014] Maleic acid, with the chemical formula C4H4O4, is an unsaturated dibasic organic acid containing two carboxyl groups (-COOH). Its molecular structure contains a carbon-carbon double bond, which gives it special chemical properties and a wide range of industrial applications. Maleic acid is a strong organic acid that can ionize into hydrogen ions (H + ), showing acidic properties. Due to the carbon-carbon double bond in its molecule, maleic acid is prone to addition reactions, polymerization reactions and other types of chemical transformations. The carboxyl group in maleic acid can ionize hydrogen ions in aqueous solution, providing an acidic environment for subsequent reactions with metal salts, and interacting with the active groups in the asphalt molecules through the carboxyl group, initially weakening the chemical bonds in the asphalt and improving the performance of the cold patch material.
[0015] Ethylene diamine (EDA) and alanine are amino organic small molecules. The chemical structure of ethylenediamine is NH2-CH2-CH2-NH2, and the chemical structure of alanine is CH3-CH(NH2)-COOH. Its amino group can be grafted onto the maleic acid molecule to achieve modification. Maleic acid modified by ethylenediamine or alanine contains both carboxyl and amino groups on its molecular chain. The amino group can undergo amidation reaction with the carboxyl group in asphalt to form a covalent bond, thereby enhancing the chemical bonding force between the initiator and the asphalt and improving the stability of the reaction. In addition, the molecular structure of ethylenediamine is relatively flexible. After reacting with maleic acid, the introduced flexible chain segment can improve the flexibility of the asphalt cold patch material. This enables the cold patch material to better adapt to the deformation of the road surface under different temperature and stress conditions and reduce the occurrence of cracks. Alanine itself is a naturally occurring amino acid that gives the asphalt cold patch material better biocompatibility.
[0016] The present invention uses copper sulfate (CuSO4) or ferric chloride (FeCl3), wherein the copper ions in copper sulfate have strong coordination ability, can effectively coordinate with carboxyl, amino and other groups to form a stable cross-linked structure, thereby significantly improving the strength and stability of the asphalt cold patch material, making it better resist the influence of vehicle load and environmental factors. The iron ions in ferric chloride have strong catalytic activity, can accelerate the reaction between maleic acid and asphalt molecules, promote the breaking and recombination of chemical bonds, make the cold patch material form higher early strength in a shorter time, shorten the maintenance time after construction, and improve the efficiency of road repair.
[0017] Preferably, the super absorbent resin is a polyacrylate having a number average molecular weight of 1000 to 8000.
[0018] Polymer resin is a functional molecular material with a three-dimensional spatial network structure. There are a large number of strongly water-absorbing groups such as carboxyl, hydroxyl, sulfonyl, and amide groups on the molecular chain. When in contact with water, external free water diffuses into the resin polymer network to form a hydrated polymer chain, making its water absorption reach hundreds or even thousands of times its own weight. The resin macromolecules are connected by hydrogen bonds to form a three-dimensional network structure, which can effectively lock water, expand rapidly, and form a gel structure, which helps the asphalt cold patch material to quickly solidify under humid conditions and improve the early strength.
[0019] As a general technical concept, the present invention also provides a method for preparing a water-reactive asphalt cold patch material, such as Figure 2 As shown, the following steps are included:
[0020] Step (1), adding maleic acid and ethylenediamine or alanine into a reactor containing deionized water, heating to a reaction temperature while stirring, and cooling to room temperature after the reaction to obtain ethylenediamine or alanine-modified maleic acid;
[0021] Step (2), adding copper sulfate or ferric chloride dropwise into step (1) under stirring, and distilling under reduced pressure after sufficient reaction to obtain a composite initiator;
[0022] Step (3), after preheating the base asphalt, add the aggregate and mineral powder thereto and stir evenly;
[0023] Step (4), continue to add the highly absorbent resin and the composite initiator prepared in step (2) to step (3), stir evenly, and obtain a water-reactive asphalt cold patch material.
[0024] Preferably, in step (1), the reaction temperature is 80°C to 150°C, and the reaction time is 5 to 10 hours.
[0025] The equation for the reaction of ethylenediamine and maleic acid is:
[0026]
[0027] The equation for the reaction of alanine and maleic acid is:
[0028]
[0029] Preferably, in step (2), the reaction time is 1 to 3 hours, the vacuum distillation pressure is 1.5 to 4 kPa, and the vacuum distillation time is 0.5 to 2 hours.
[0030] Preferably, in step (3), the preheating temperature is 85-100° C., the preheating time is 2-4 hours, and the stirring time is 2-5 minutes.
[0031] Preferably, in step (4), the stirring time is 3 to 12 minutes.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The composite initiator is used in the present invention. When the composite initiator contacts water, maleic acid first dissolves and ionizes hydrogen ions: The generated hydrogen ions make the aqueous solution acidic, which causes the relatively weak chemical bonds such as ester bonds and carbon-hydrogen bonds in the asphalt to undergo a certain degree of hydrolysis and breakage, forming reactive free radicals and functional groups, such as At the same time, iron salts or copper salts dissociate into metal ions in water: The metal ions can react with the hydrolyzed carboxyl groups in the asphalt: and Cross-linking is formed to form a more stable and complex three-dimensional network structure. During the entire reaction process, the acidic effect of maleic acid and the metal ion coordination effect of iron salts or copper salts work together to control the chemical bond breaking and recombination of asphalt molecules, further enhancing the strength of asphalt cold patch materials, increasing water stability and durability. Maleic acid modified with ethylenediamine or alanine adds amino groups to the original molecular chain, and the amino groups can react with the carboxyl groups in the asphalt to form covalent bonds, further enhancing the chemical bonding between the initiator and the asphalt, thereby further improving the overall performance of the asphalt cold patch material.
[0034] (2) The present invention uses a highly water-absorbent resin, which has a large number of strong water-absorbent groups such as carboxyl, hydroxyl, sulfonyl, and amide groups on its molecular chain. After absorbing water, it can be quickly solidified to form early strength, which is conducive to rapid traffic.
[0035] (3) The components used in the present invention are green and environmentally friendly, without volatile solvents, and are environmentally friendly. The prepared asphalt cold patch material has fast curing, high strength, and good water stability, which is conducive to promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a picture showing the effect of the asphalt cold patch material prepared in Example 1 on repairing potholes in the road surface.
[0037] Figure 2 Flow chart for preparing water-reactive asphalt cold patch material. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention are described in detail below, and the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention. The present invention is further described below in conjunction with specific embodiments.
[0039] Unless otherwise specified in the examples of the present invention, the various components and chemical reagents used were obtained through conventional commercial channels:
[0040] Limestone ore and basalt powder come from Lingshou County Huixin Mining Processing Plant.
[0041] No. 70, No. 90, and No. 110 base asphalts were purchased from Hengshui Zehao Chemical Co., Ltd.
[0042] Maleic acid was from Shandong Hui'an Chemical Co., Ltd.
[0043] Ethylenediamine and alanine were purchased from Jinan Liyang Chemical Co., Ltd.
[0044] Ferric chloride and copper sulfate were purchased from Jiangsu Muhong Environmental Protection Technology Co., Ltd.
[0045] Polyacrylate was obtained from Jining Sanyuan Chemical Technology Co., Ltd.
[0046] Example 1
[0047] A water-reactive asphalt cold patch material includes the following components by weight: 600 parts of LB-10 limestone mineral material, 60 parts of basalt mineral powder, 110 parts of No. 70 base asphalt, 5 parts of composite initiator and 2 parts of polyacrylate. The LB-10 grade of the limestone is shown in Table 1.
[0048] Table 1 LB-10 type gradation
[0049]
[0050] The preparation method of the water-reactive asphalt cold patch material is as follows:
[0051] (1) adding maleic acid and alanine into a reactor containing deionized water, heating to 120° C. while stirring, reacting for 8 hours, and cooling to room temperature after the reaction to obtain alanine-modified maleic acid, wherein the mass of alanine is 30% of the mass of maleic acid;
[0052] (2) copper sulfate accounting for 60% of the mass of maleic acid is added dropwise to step (1) under stirring, and after sufficient reaction for 3 hours, it is distilled under reduced pressure at a pressure of 3 kPa for a distillation time of 1 hour to obtain a composite initiator;
[0053] (3) After preheating 110 parts of No. 70 base asphalt at 100°C for 2 hours, add 600 parts of limestone ore and 60 parts of basalt ore powder and stir thoroughly for 5 minutes;
[0054] (4) Add 2 parts of polyacrylate and 5 parts of the composite initiator obtained in step (2) to step (3) and stir thoroughly for 10 minutes to obtain a water-reactive asphalt cold patch material.
[0055] The effect of the asphalt cold patch material prepared in Example 1 on repairing potholes in the road is shown in the figure Figure 1 shown.
[0056] Example 2
[0057] A water-reactive asphalt cold patch material comprises the following components in parts by weight: 580 parts of LB-10 limestone mineral material, 50 parts of basalt mineral powder, 120 parts of No. 70 base asphalt, 8 parts of composite initiator and 1 part of polyacrylate.
[0058] The preparation method of the water-reactive asphalt cold patch material is as follows:
[0059] (1) adding maleic acid and ethylenediamine into a reactor containing deionized water, heating to 150° C. while stirring, reacting for 5 hours, and cooling to room temperature after the reaction to obtain ethylenediamine-modified maleic acid, wherein the mass of ethylenediamine is 50% of the mass of maleic acid;
[0060] (2) copper sulfate accounting for 80% of the mass of maleic acid is added dropwise to step (1) under stirring, and after sufficient reaction for 1 hour, it is distilled under reduced pressure at a pressure of 4 kPa for a distillation time of 2 hours to obtain a composite initiator;
[0061] (3) Preheat 120 parts of No. 70 base asphalt at 90°C for 4 hours, add 580 parts of limestone and 50 parts of basalt powder, and stir thoroughly for 4 minutes;
[0062] (4) Add 1 part of polyacrylate and 8 parts of the composite initiator obtained in step (2) to step (3) and stir thoroughly for 12 minutes to obtain a water-reactive asphalt cold patch material.
[0063] Example 3
[0064] A water-reactive asphalt cold patch material comprises the following components in parts by weight: 550 parts of LB-10 limestone mineral material, 40 parts of basalt mineral powder, 80 parts of No. 70 base asphalt, 7 parts of composite initiator and 3 parts of polyacrylate.
[0065] The preparation method of the water-reactive asphalt cold patch material is as follows:
[0066] (1) adding maleic acid and ethylenediamine into a reactor containing deionized water, heating to 100° C. while stirring, reacting for 6 hours, and cooling to room temperature after the reaction to obtain ethylenediamine-modified maleic acid, wherein the mass of ethylenediamine is 20% of the mass of maleic acid;
[0067] (2) adding ferric chloride accounting for 70% of the mass of maleic acid dropwise to step (1) under stirring, and after sufficient reaction for 2 hours, distilling under reduced pressure at a pressure of 1.5 kPa for a distillation time of 0.5 hours to obtain a composite initiator;
[0068] (3) After preheating 80 parts of No. 70 base asphalt at 85°C for 3 hours, add 550 parts of limestone and 40 parts of basalt powder and stir thoroughly for 2 minutes;
[0069] (4) Add 3 parts of polyacrylate and 7 parts of the initiator obtained in step (2) to step (3) and stir thoroughly for 3 minutes to obtain a water-reactive asphalt cold patch material.
[0070] Example 4
[0071] A water-reactive asphalt cold patch material comprises the following components in parts by weight: 540 parts of LB-10 limestone mineral material, 58 parts of basalt mineral powder, 105 parts of No. 90 base asphalt, 6 parts of composite initiator and 4 parts of polyacrylate.
[0072] The preparation method of the water-reactive asphalt cold patch material is as follows:
[0073] (1) adding maleic acid and alanine into a reactor containing deionized water, heating to 130° C. while stirring, reacting for 7 hours, and cooling to room temperature after the reaction to obtain alanine-modified maleic acid, wherein the mass of alanine is 10% of the mass of maleic acid;
[0074] (2) copper sulfate accounting for 50% of the mass of maleic acid is added dropwise to step (1) under stirring, and after sufficient reaction for 1.5 hours, it is distilled under reduced pressure at a pressure of 3.5 kPa for a distillation time of 1.5 hours to obtain a composite initiator;
[0075] (3) Preheat 105 parts of No. 90 base asphalt at 98°C for 2.5 hours, add 540 parts of limestone and 58 parts of basalt powder, and stir thoroughly for 4.5 minutes;
[0076] (4) 4 parts of polyacrylate and 6 parts of the composite initiator obtained in step (2) are added to step (3) and stirred for 9 minutes to obtain a water-reactive asphalt cold patch material.
[0077] Example 5
[0078] A water-reactive asphalt cold patch material comprises the following components in parts by weight: 535 parts of LB-10 limestone mineral material, 56 parts of basalt mineral powder, 100 parts of No. 90 base asphalt, 4 parts of composite initiator and 5 parts of polyacrylate.
[0079] The preparation method of the water-reactive asphalt cold patch material is as follows:
[0080] (1) adding maleic acid and ethylenediamine into a reactor containing deionized water, heating to 90° C. while stirring, reacting for 9 hours, and cooling to room temperature after the reaction to obtain ethylenediamine-modified maleic acid, wherein the mass of ethylenediamine is 45% of the mass of maleic acid;
[0081] (2) copper sulfate accounting for 45% of the mass of maleic acid is added dropwise to step (1) under stirring, and after sufficient reaction for 2.5 hours, it is distilled under reduced pressure at a pressure of 2.5 kPa for a distillation time of 1 hour to obtain a composite initiator;
[0082] (3) Preheat 90 parts of No. 90 base asphalt at 96°C for 3.5 hours, add 535 parts of limestone and 56 parts of basalt powder, and stir thoroughly for 2 minutes;
[0083] (4) Add 5 parts of polyacrylate and 4 parts of the composite initiator obtained in step (2) to step (3) and stir thoroughly for 5 minutes to obtain a water-reactive asphalt cold patch material.
[0084] Example 6
[0085] A water-reactive asphalt cold patch material comprises the following components in parts by weight: 530 parts of LB-10 limestone mineral material, 54 parts of basalt mineral powder, 65 parts of No. 90 base asphalt, 3 parts of composite initiator and 6 parts of polyacrylate.
[0086] The preparation method of the water-reactive asphalt cold patch material is as follows:
[0087] (1) adding maleic acid and alanine into a reactor containing deionized water, heating to 110° C. while stirring, reacting for 5.5 hours, and cooling to room temperature after the reaction to obtain alanine-modified maleic acid, wherein the mass of alanine is 25% of the mass of maleic acid;
[0088] (2) adding ferric chloride accounting for 30% of the mass of maleic acid dropwise to step (1) under stirring, reacting for 2.5 hours, and then distilling under reduced pressure at a pressure of 2.5 kPa for 1.5 hours to obtain a composite initiator;
[0089] (3) Preheat 65 parts of No. 90 base asphalt at 85°C for 4 hours, add 530 parts of limestone and 54 parts of basalt powder, and stir thoroughly for 2.5 minutes;
[0090] (4) Add 6 parts of polyacrylate and 3 parts of the composite initiator obtained in step (2) to step (3) and stir thoroughly for 4 minutes to obtain a water-reactive asphalt cold patch material.
[0091] Example 7
[0092] A water-reactive asphalt cold patch material comprises the following components in parts by weight: 520 parts of LB-10 limestone mineral material, 52 parts of basalt mineral powder, 92 parts of No. 110 base asphalt, 2 parts of composite initiator and 8 parts of polyacrylate.
[0093] The preparation method of the water-reactive asphalt cold patch material is as follows:
[0094] (1) adding maleic acid and alanine into a reactor containing deionized water, heating to 80° C. while stirring, reacting for 6.5 hours, and cooling to room temperature after the reaction to obtain alanine-modified maleic acid, wherein the mass of alanine is 35% of the mass of maleic acid;
[0095] (2) adding ferric chloride accounting for 40% of the mass of maleic acid dropwise to step (1) under stirring, reacting for 1.5 hours, and then distilling under reduced pressure at a pressure of 3 kPa for 1 hour to obtain a composite initiator;
[0096] (3) Preheat 92 parts of No. 110 base asphalt at 88°C for 3.5 hours, add 520 parts of limestone and 52 parts of basalt powder, and stir thoroughly for 2 minutes;
[0097] (4) 8 parts of polyacrylate and 2 parts of the composite initiator obtained in step (2) are added to step (3) and stirred for 3 minutes to obtain a water-reactive asphalt cold patch material.
[0098] Example 8
[0099] A water-reactive asphalt cold patch material comprises the following components in parts by weight: 510 parts of LB-10 limestone mineral material, 43 parts of basalt mineral powder, 83 parts of No. 110 base asphalt, 1 part of composite initiator and 9 parts of polyacrylate.
[0100] The preparation method of the water-reactive asphalt cold patch material is as follows:
[0101] (1) adding maleic acid and ethylenediamine into a reactor containing deionized water, heating to 80° C. while stirring, reacting for 7.5 hours, and cooling to room temperature after the reaction to obtain ethylenediamine-modified maleic acid, wherein the mass of ethylenediamine is 15% of the mass of maleic acid;
[0102] (2) adding ferric chloride accounting for 55% of the mass of maleic acid dropwise to step (1) under stirring, reacting for 2 hours, and then distilling under reduced pressure at a pressure of 2 kPa for 2 hours to obtain a composite initiator;
[0103] (3) After preheating 83 parts of No. 110 base asphalt at 94°C for 2.5 hours, add 510 parts of limestone and 43 parts of basalt powder and stir thoroughly for 3 minutes;
[0104] (4) 9 parts of polyacrylate and 1 part of the composite initiator obtained in step (2) are added to step (3) and stirred for 7 minutes to obtain a water-reactive asphalt cold patch material.
[0105] Example 9
[0106] A water-reactive asphalt cold patch material comprises the following components in parts by weight: 500 parts of LB-10 limestone mineral material, 42 parts of basalt mineral powder, 72 parts of No. 110 matrix asphalt, 0.5 parts of composite initiator and 10 parts of polyacrylate.
[0107] The preparation method of the water-reactive asphalt cold patch material is as follows:
[0108] (1) adding maleic acid and ethylenediamine into a reactor containing deionized water, heating to 95° C. while stirring, reacting for 8.5 hours, and cooling to room temperature after the reaction to obtain ethylenediamine-modified maleic acid, wherein the mass of ethylenediamine is 35% of the mass of maleic acid;
[0109] (2) copper sulfate accounting for 56% of the mass of maleic acid is added dropwise to step (1) under stirring, and after sufficient reaction for 2 hours, it is distilled under reduced pressure at a pressure of 1.5 kPa and a distillation time of 0.5 hours to obtain a composite initiator;
[0110] (3) Preheat 72 parts of No. 110 base asphalt at 91°C for 4 hours, add 500 parts of limestone and 42 parts of basalt powder, and stir thoroughly for 5 minutes;
[0111] (4) 10 parts of polyacrylate and 0.5 parts of the composite initiator obtained in step (2) are added to step (3) and stirred for 8 minutes to obtain a water-reactive asphalt cold patch material.
[0112] Comparative Example 1
[0113] A method for preparing a water-reactive asphalt cold patch material, except that it does not contain a highly absorbent resin, the remaining steps are the same as those of Example 1.
[0114] Comparative Example 2
[0115] A method for preparing a water-reactive asphalt cold patch material, except that the composite initiator is not included, the remaining steps are the same as those of Example 1.
[0116] Comparative Example 3
[0117] A method for preparing a solvent-based asphalt cold patch material, comprising the following components by weight: 100 parts of No. 70 base asphalt, 10 parts of No. 10 diesel, 10 parts of heavy oil, 1 part of coumarone resin, 10 parts of C1 aromatic solvent oil, 1 part of lignin, 0.2 parts of fatty alcohol polyoxyethylene ether, and 0.5 parts of PA-1 anti-stripping agent. The specific preparation process comprises the following steps:
[0118] (1) 100 parts of No. 70 base asphalt were heated to a molten state, and then 10 parts of No. 10 diesel were added thereto, and the asphalt was diluted by a high-speed shearing machine with a rotation speed of 2000 r / min for about 10 minutes to prepare prepolymer A;
[0119] (2) 10 parts of heavy oil were heated to 80° C. in a reactor, 1 part of coumarone resin was added, and the mixture was stirred evenly to prepare prepolymer B. The shearing time was about 10 min.
[0120] (3) heating 10 parts of C1 aromatic solvent oil to 50° C. in a reaction kettle, adding 1 part of wood cellulose, 0.2 parts of fatty alcohol polyoxyethylene ether and 0.5 parts of PA-1 anti-stripping agent in the above-mentioned weight parts in sequence, and uniformly stirring to prepare prepolymer C, with a shearing time of about 15 min;
[0121] (4) The mixture of the prepolymers A, B and C is uniformly stirred in a reactor for about 10 minutes to prepare a cold patch asphalt liquid; and then uniformly stirred with the aggregate to obtain a solvent-based asphalt cold patch material.
[0122] Performance Test:
[0123] The water-reactive asphalt cold patch materials prepared in Examples 1-9 and the asphalt cold patch materials prepared in Comparative Examples 1-3 were selected for performance testing, wherein the cold patch materials prepared in Examples 1-9 and Comparative Examples 1-2 were added with 2% of their weight of water and stirred for 30 seconds before testing. The Marshall test, beam bending test, and freeze-thaw splitting test methods refer to JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", and the cohesiveness test refers to JTG F40-2004 "Technical Specifications for Highway Asphalt Pavement Construction" to obtain the performance test results as shown in Table 2:
[0124] Table 2 Performance test results of water-reactive asphalt cold patch materials prepared in Examples 1-9 and Comparative Examples 1-3
[0125]
[0126] The initial Marshall stability and the forming Marshall stability can well demonstrate the strength of the prepared asphalt cold patch material. According to the technical requirements in JTG E20-2011 "Testing Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", the forming Marshall stability needs to be ≥3kN. Examples 1 to 9 all meet the technical requirements, and the minimum forming Marshall stability is 5.23kN, which is higher than the comparative example 1 without super absorbent resin, the comparative example 2 without composite initiator, and the solvent-based asphalt cold patch material comparative example 3. This is because the asphalt cold patch material containing polyacrylate can quickly undergo a curing reaction after reacting with water, which enhances the bonding effect, and the addition of the composite initiator can effectively form a cross-linked network, which can also play a role in enhancing the bonding performance between asphalt cold patches. Combined with Table 2, with the increase of the content of polyacrylate, the initial Marshall stability and the forming Marshall stability of the water-reactive asphalt cold patch material first increase and then decrease.
[0127] Cold patch materials need to have good crack resistance under low temperature conditions, and good low temperature performance is the prerequisite for cold patch materials to be used in pothole repair. According to the technical requirements in the specification, in the beam bending test, the maximum bending strain value of the cold patch material in the winter cold zone should be greater than 2500με, and Examples 1 to 9 all meet the requirements, while Comparative Examples 1, 2 and 3 all fail to meet the requirements, especially Comparative Examples 2 and 3, where the maximum bending strain value of the beam bending is only about 1500με. This is because in the composite initiator, the modified maleic acid and metal salts are cross-linked with the asphalt, and the criss-cross three-dimensional multi-directional distribution in the asphalt cold patch material can effectively improve the low-temperature deformation resistance of the cold patch material.
[0128] The initial splitting tensile strength of Examples 1 to 9 is all ≥0.32MPa, and the formed splitting tensile strength is ≥0.52MPa, indicating that the prepared asphalt cold patch material can withstand the traffic load after repair and meet the needs of rapid traffic. When polyacrylate and maleic acid and iron salt or copper salt modified by ethylenediamine or alanine are added, its splitting tensile strength is improved to varying degrees. As the content of maleic acid and iron or copper salt modified by ethylenediamine or alanine increases, the splitting tensile strength shows a trend of first increasing and then decreasing. This is because the maleic acid and iron or copper salt modified by ethylenediamine or alanine can cooperate with each other to form more and more stable cross-linked structures, thereby optimizing the internal structure of the asphalt cold patch material, so that the asphalt cold patch material can better resist the splitting load and thus have a stronger splitting tensile strength. Then, when the content of maleic acid and iron or copper salt modified by ethylenediamine or alanine is too high, excessive cross-linking causes the cold patch material to become brittle as a whole. When subjected to splitting loads, the over-cross-linked structure cannot effectively disperse stress through deformation and is prone to brittle failure. Therefore, its splitting tensile strength will show a trend of first increasing and then decreasing.
[0129] After potholes are repaired with cold patch materials, it is necessary to ensure that there will be no loosening, threshing and other defects due to vehicle load or natural conditions. This requires the cold patch material to have good cohesiveness. As can be seen from Table 2, the cohesiveness of Examples 1 to 9 is ≥ 70%, indicating that the water-reactive asphalt cold patch material prepared by the present invention has good adhesion and can effectively avoid problems such as loosening and falling off.
[0130] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A water-reactive asphalt cold patch material, characterized in that: The invention comprises the following components in parts by weight: 500 to 600 parts of aggregate, 40 to 60 parts of mineral powder, 65 to 120 parts of base asphalt, 0.5 to 8 parts of composite initiator and 1 to 10 parts of highly absorbent resin; Wherein, the composite initiator is a composition of iron salt or copper salt and maleic acid modified by ethylenediamine or alanine.
2. A water-reactive asphalt cold patch material according to claim 1, characterized in that: The aggregate is limestone ore, the gradation type of the aggregate is LB-10, and the mineral powder is basalt mineral powder.
3. The water-reactive asphalt cold patch material according to claim 1, characterized in that: The base asphalt is any one of No. 70 base asphalt, No. 90 base asphalt, and No. 110 base asphalt.
4. The water-reactive asphalt cold patch material according to claim 1, characterized in that: The iron salt is ferric chloride; the copper salt is selected from copper sulfate; the mass of the ethylenediamine or alanine is 10-50% of the mass of the maleic acid; the mass of the ferric chloride or copper sulfate is 20-80% of the mass of the maleic acid.
5. The water-reactive asphalt cold patch material according to claim 1, characterized in that: The highly water-absorbent resin is a polyacrylate with a number average molecular weight of 1000 to 8000.
6. A method for preparing a water-reactive asphalt cold patch material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step (1): adding maleic acid and ethylenediamine or alanine into a reactor containing deionized water, heating the mixture to a reaction temperature while stirring, and cooling the mixture to room temperature after the reaction to obtain maleic acid modified with ethylenediamine or alanine; Step (2): adding copper sulfate or ferric chloride dropwise to step (1) under stirring, and distilling under reduced pressure after sufficient reaction to obtain a composite initiator; Step (3): After preheating the base asphalt, add aggregate and mineral powder thereto and stir evenly; Step (4): Continue to add the highly absorbent resin and the composite initiator prepared in step (2) to step (3), stir evenly, and obtain a water-reactive asphalt cold patch material.
7. The method for preparing a water-reactive asphalt cold patch material according to claim 6, characterized in that: In the step (1), the reaction temperature is 80°C to 150°C, and the reaction time is 5 to 10 hours.
8. The method for preparing a water-reactive asphalt cold patch material according to claim 6, characterized in that: In the step (2), the reaction time is 1 to 3 hours, the vacuum distillation pressure is 1.5 to 4 kPa, and the vacuum distillation time is 0.5 to 2 hours.
9. The method for preparing a water-reactive asphalt cold patch material according to claim 6, characterized in that: In the step (3), the preheating temperature is 85-100° C., the preheating time is 2-4 hours, and the stirring time is 2-5 minutes.
10. The method for preparing a water-reactive asphalt cold patch material according to claim 9, characterized in that: In the step (4), the stirring time is 3 to 12 minutes.
Citation Information
Patent Citations
Organic-inorganic compound alkali-free flash setting admixture and preparation method thereof
CN107963827A
Composite asphalt mixture suitable for high-latitude or high-altitude area
CN108484001A
Preparation method of chemical reaction type cold patch asphalt mixture
CN112851174A
Polyaspartic acid derivative as well as preparation method and application thereof
CN117362643A
Water reaction type asphalt cold patch material as well as preparation method and use method thereof
CN117700155A